First Hypotheses about the Emergence of ‘Sex’ Segregated Toilets in Primary Schools. Buenos Aires - da Silva, Maria Lucila (Historia y Memoria de la Educación, 2023)
This article, based on a study of the introduction of toilets in primary schools in Buenos Aires, Argentina, is part of a line of research that locates the emergence of binary definitions of sex, gender and sexuality as we know them (associated with a set of behaviours, gestures, corporalities, and values), between the mid-nineteenth century and the early twentieth century. There is consensus regarding the central role that primary schooling has played in regulating gender and sexuality along cis and heterosexual norms. As this study shows, school architecture was one of the technologies that worked in this sense. At the end of the nineteenth century the practicality of «men» and «women» sharing educational spaces was widely discussed. However, the practice of marking toilets in primary schools according to «sex» had not yet become widespread. The aim of this article is to identify practices and discourses related to spatial «sex»» segregation regarding primary school toilets. We argue that the «sexual» segregation of toilets is part of a series of discourses and practices that have operated since the end of the nineteenth century, producing two hegemonic and excluding sex-gender figures: «man» and «woman».